(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Development of Mathematical Confidence Instruments in Linear Program Materials "Thesis of Mathematics Education Department, Faculty of Tarbiyah and Teacher Training, Syarif Hidayatullah State Islamic University, Jakarta, June 2021. This study aims to develop a special confidence instrument for linear programming material. The indicators of self-confidence according to Lauster and Hendriana in this study are belief in one’s own abilities, act independently in making decisions, have a positive self-concept and dare to express opinions, the instrument developed in the form of a non-test instrument as many as 60 questionnaires were tested on 127 class students. XI MAN 2 Tangerang City and SMAIT Tunas Harapan Divine. The development model applied is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results showed that the developed mathematical confidence instrument met the eligibility criteria based on the results of expert tests, based on empirical tests as many as 4 instruments were declared invalid and had a very high level of reliability.